Representativeness of the Arosa/Davos Measurements for the Analysis of the Global Total Column Ozone Behavior - Rozanov, Eugene; Egorova, Tatiana; Egli, Luca; Karagodin-Doyennel, Arseniy; Sukhodolov, Timofei; Schill, Herbert; Stübi, Rene; Gröbner, Julian (Frontiers in Earth Science, 2021)
The study investigates the representativeness of the total column ozone (TCO) measurements from the ground-based instruments located at the Arosa/Davos stations in Switzerland to analyze the global ozone layer behavior in the past and future. The statistical analysis of the satellite and model data showed a high correlation of the ground-based TCO data with the near-global and northern hemisphere annual mean TCO for the 1980–2018 period. Addition of the Arosa/Davos TCO data as a proxy to the set of standard explanatory variables for multiple linear regression analysis allows estimating the TCO behavior from 1926 up to the present day. We demonstrate that the real-time measurements and high homogeneity level of the Arosa/Davos TCO time series are also beneficial for quick estimates of the future ozone layer recovery.